Investigation of the Relationship between Cognitive Behavioral Physical Activity and Multiple Intelligence Levels in Different Team Sports Athletes - Okudan, Bilal (Progress in Nutrition, 2021)
Study Objectives: This study aimed to examine the relationship between cognitive behavioral physical activity and multiple intelligence levels of athletes in different team sports. Methods: The sample of the study consisted of 518 athletes dealing with different team sports. As a data collection tool, "Cognitive Behavioral Physical Activity Scale" developed by Schembre et al. (2015) and adapted into Turkish by Eskiler et al. (2016), and "Multiple Intelligence Scale" developed by Gardner (1990) and adapted into the Turkish Selçuk et al. (2003), were used. In the analysis of the data, it was determined that the data did not show normal distribution as a result of the Kolmogorov-Smirnov test, and non-parametric analysis was used. Mann-Whitney U test was used for paired comparisons and the Kruskal Wallis-H test was used for multiple comparisons. Results: It was determined that female athletes had higher result expectation from cognitive behavioral physical activity sub-dimensions, while males' personal disabilities were higher than female. When multiple intelligence levels were examined, although the logical intelligence levels of male were higher than female, it was found that their kinesthetic intelligence levels were higher. Also, when compared according to sports branches, it was found that the logical intelligence levels of basketball players were higher than futsal players. Finally, when the relationship between the cognitive behavioral physical activity levels of athletes and multiple intelligence sub-dimensions was examined, it was found that there was a positive relationship between cognitive behavioral physical activity and intelligence types.  These results showed that as the level of cognitive behavioral physical activity increased, the mean that individuals can obtain from the multiple intelligence scale can increase. Conclusion: These results suggested that especially sedentary individuals should be directed to physical activities starting from adolescence. Thus, they can contribute to the development of multiple intelligences.